Decision Support System Analysis Method Technique For Preference By Order To Ideal Solution Similarity (TOPSIS) - Handayani W; Erlangga Erlangga (Bandar Lampung University (UBL), 2017)
In some circumstances, sometimes people are faced with several options. Such as selecting school, choose a subject, choose a place of residence, employment and others. Determining the choice was not easy, making indecisive and difficult to take decisions. And sometimes people pay less attention to the positive and negative impacts in making a decision, as well as the lack of attention to aspects or essential criteria required. Moreover, if the wrong decision, can be bad for the man himself. Therefore, it is necessary Decision Support Systems. Decision Support System (DSS) or Decision Support System (DSS) is a system that can provide problem-solving ability and the ability of communicating to a problem with the condition of semi-structured and unstructured. This system is used to assist decision-making in situations of semi-structured and unstructured situations, where no one knows for sure how the decision should be made (Turban, 2001). The method used by the author in the Decision Support System is a method Technique for Order Preference by Similarity to Ideal Solution (TOPSIS)